Peningkatan Pemahaman Literasi Digital dalam Upaya Minimalisasi Pelanggaran Hukum Bagi Pelajar - Septiandani, Dian; Sjafiie, Sri Syamsiyah Lestari; Pamungkas, Yoma Bagus (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2024)
Information technology is increasingly advanced and developing, greatly influencing people's activities, including students. Advances in information and communication technology in the current digital age have changed the way society interacts. Rapid technological developments have provided significant benefits to social life. Apart from the benefits that can be obtained, it turns out that this progress can also give rise to the potential for committing legal violations. To increase students' understanding of digital literacy and the importance of knowledge of it to minimize legal violations for students, outreach is carried out. The way this is done is by lecture and question and answer directly after the lecture is finished. The output of this PkM activity is the publication of the PkM journal, mass media publications (print/online), IPR in the form of posters, implementation videos uploaded on YouTube, and increased understanding.